Histology of Caenagnathid (Theropoda, Oviraptorosauria) Dentaries and Implications for Development, Ontogenetic Edentulism, and Taxonomy. Issue 4 (4th July 2019) - Funston, Gregory F.; Wilkinson, Ryan D.; Simon, D. Jade; Leblanc, Aaron H.; Wosik, Mateusz; Currie, Philip J.
ABSTRACT: The fossil record of caenagnathid oviraptorosaurs consists mainly of their fused, complexly sculptured dentaries, but little is known about the growth and development of this diagnostic structure. Previous work has suggested that the ridges and grooves on the occlusal surface are either the vestiges of teeth and their alveoli or were adaptations to increase shearing action during mastication. In addition, the distinctiveness of the dentaries has led to their use for species‐level taxonomy, without a complete understanding of their variation through ontogeny. Here, we describe additional caenagnathid mandibles from the Dinosaur Park Formation of Alberta, Canada, and perform histological analyses to assess relative ontogenetic stage and the nature of the occlusal elaborations. The results show that the mandibular symphysis is synostosed early in ontogeny and does not accurately reflect ontogenetic stage in caenagnathids. In contrast, the presence of cyclical growth marks in a large specimen shows that mandibles can be used for relative histological maturity estimation. Histological features of the ridges of bone surrounding the lingual groove indicate that they are not the vestiges of tooth‐bearing tissues and that caenagnathids did not lose their teeth through ontogeny as suggested in previous work. Instead, increased secondary remodeling in these structures is consistent with their use for food processing. Unexpectedly advanced maturity in a small specimen suggests that at least three caenagnathid species of varying body sizes coexisted in the Dinosaur Park Formation. These results stress the necessity of histological analysis when assessing maturity or ontogenetic trends in fossil material. Anat Rec, 303:918–934, 2020. © 2019 Wiley Periodicals, Inc.